Will Markets Provide Humane Jobs? A Hypothesis - Arash Nekoei (Center for Economic Studies and ifo Institute (CESifo), 2022)
Most of the key amenities of our today jobs did not emerge in private contracts; instead, they appeared in collective agreements and regulations. I argue that understanding this observation can guide the provision of future amenities. I show that markets underprovide an amenity if workers who value it more have a lower average unobserved productivity. Universal mandate of such amenities improves social welfare when taste-productivity correlation is high. Policies that leverage heterogeneity in the taste-productivity correlation by observable characteristics, e.g., quota and tagging, dominate mandate in the presence of a mild adverse selection.
Keywords: 330